Mental Health Risk Factors and Coping Strategies among Students in Asia Pacific during COVID-19 Pandemic-A Scoping Review - Wandeep, Kaur; Vimala, Balakrishnan; Chen, Yoke Yong; Jeyarani, Periasamy (Molecular Diversity Preservation International (MDPI), 2022)
The impact of COVID-19 has forced higher education institutes to go into lockdown in order to curb the situation. This sudden change caused students within the institutions to forgo traditional face to face classroom settings and to attend immediate online classes. This review aims to summarize the evidence of the social demographic mental health impacts of the COVID-19 pandemic on students in higher education institutes within the Asia Pacific region and identify the coping mechanisms adopted during these times. A systematic literature search was conducted using three databases (PubMed, Google Scholar, and Scopus), out of which 64 studies met the inclusion/exclusion criteria. The findings revealed that the social demographic groups most at risk were female students, those who were in the final years of their studies (i.e., students who were almost graduating), and postgraduate students as well as students studying medical fields (nursing, dental, medicine, health sciences etc.). The majority of the studies identified that students were relying on mobile devices and extended screen time to cope with the pandemic. Having proper social support, be it through a network of friends or positive family cohesion, can be a good buffer against the mental impacts of COVID-19. Students in higher education institutes are at risk of mental consequences due to COVID-19. By reducing their screen time, finding a healthier coping system, increasing the availability of support within the family and community, as well as actively engaging in beneficial activities students may be able to alleviate general negative emotions, specifically during the pandemic.